Insights to Identifying and Managing Pain in Persons With Dementia in Long-Term Care: A Mixed Methods Study Comparing the Abbey Pain Scale and Pain Assessment in Advanced Dementia Scale - Parkman, Suzanne; Mastel, -Smith Beth; McGuire, Anthony; Duke, Gloria (Journal of Gerontological Nursing, 2021)
Pain is usually identified by specific behaviors driven by the need for relief; however, persons with dementia present a unique challenge for nurses in assessing and managing pain. The aim of this mixed methods study was to explore the relationship between two observational pain scales, expressed need-driven behaviors, and likelihood of medication administration for persons with dementia. The qualitative strand examined nurses' perceptions regarding facilitators and barriers to pain scale use. Quantitative data analysis indicated the Abbey Pain Scale was significantly correlated with behaviors (r[26] = 0.41, p < 0.05) and approached significance with medication administration (r[26] = 0.35, p = 0.067). Qualitative analysis identified three core themes: (a) Challenges in Assessing Persons With Dementia for Pain; (b) Facilitators and Barriers to Pain Management; and (c) Difficulty Caring for Persons With Dementia. Clinical implications suggest the need for a systematic, consistent method of observing pain-related behaviors in persons with dementia. [Journal of Gerontological Nursing, 47(2), 21–30.]